Regulation of motor activity of ciliary outer-arm dynein by the light chain 1; Implications from the structure of the light chain bound to the microtubule-binding domain of the heavy chain - Toshiki Yagi; Akiyuki Toda; Muneyoshi Ichikawa; Genji Kurisu (Biophysics and Physicobiology, 2023)
Ciliary bending movements are powered by motor protein axonemal dyneins. They are largely classified into two groups, inner-arm dynein and outer-arm dynein. Outer-arm dynein, which is important for the elevation of ciliary beat frequency, has three heavy chains (α, β, and γ), two intermediate chains, and more than 10 light chains in green algae, Chlamydomonas. Most of intermediate chains and light chains bind to the tail regions of heavy chains. In contrast, the light chain LC1 was found to bind to the ATP-dependent microtubule-binding domain of outer-arm dynein γ-heavy chain. Interestingly, LC1 was also found to interact with microtubules directly, but it reduces the affinity of the microtubule-binding domain of γ-heavy chain for microtubules, suggesting the possibility that LC1 may control ciliary movement by regulating the affinity of outer-arm dyneins for microtubules. This hypothesis is supported by the LC1 mutant studies in Chlamydomonas and Planaria showing that ciliary movements in LC1 mutants were disordered with low coordination of beating and low beat frequency. To understand the molecular mechanism of the regulation of outer-arm dynein motor activity by LC1, X-ray crystallography and cryo-electron microscopy have been used to determine the structure of the light chain bound to the microtubule-binding domain of γ-heavy chain. In this review article, we show the recent progress of structural studies of LC1, and suggest the regulatory role of LC1 in the motor activity of outer-arm dyneins. This review article is an extended version of the Japanese article, The Complex of Outer-arm Dynein Light Chain-1 and the Microtubule-binding Domain of the Heavy Chain Shows How Axonemal Dynein Tunes Ciliary Beating, published in SEIBUTSU BUTSURI Vol. 61, p. 20–22 (2021).